Cidadania como mercadoria? A legitimação do status cidadão através do consumo de livros - Baltazar, Caroline Campanha (2019)
In this work we study the relationship between citizenship and consumption. However, in addition to consumption as a citizen practice, our research sought to investigate whether books, as consumer goods, that is, merchandise, also act in the exercise of citizenship. Our theoretical contribution on consumption articulated in the citizenship counted on Canclini (1999) and Demo (1995), both authors identify in the consumption an act of the citizen practice. The first highlights participation in the consumption process. The second author works on the concept of emancipatory citizenship. In this concept citizenship is exercised when the individual breaks with political poverty and, thus, the citizen takes for himself the understanding of the exercise of citizenship. As a consequence of this 'internal' process consumption appears as a possibility to exercise citizenship, but in this context the market occupies a middle position, not end. In this way, the citizen makes use of the market to heal his needs as citizens. To contextualize the book as a commodity, we go through consumer studies, using Miller (2013) to understand objects within material culture, in addition to Douglas and Isherwood (2004) who also discuss objects and their meanings. The authors point out that the meaning of the commodity is given by those who use them and that these meanings are created to contextualize us within our reality. Therefore, we analyze the book as a commodity, according to its utilitarian, commercial and sociocultural meaning (SANTAELLA; NOTH, 2009). In order to study the phenomenon we chose as the locus of research the subscribers of the book club TAG-LITERARY EXPERIENCES, the choice of the respondents was for convenience. We used three types of research to build this work: bibliographic research, semi-structured interviews and documentary analysis. For the analysis of the data collected, we used the technique of Collective Subject Discourse Analysis (DSC) (LEFEVRE and LEFEVRE, 2009). The results explained that, for respondents, consumption is a way of exercising citizenship, and that books, as commodities consumed, are means for the exercise of it, due to its relation with education, information, culture, development of critical thinking , besides being also a consumer good, which as such is part of the economic process of consumption, which is inserted in the citizen's practice .